A new jeholornithiform exhibits the earliest appearance of the fused sternum and pelvis in the evolution of avialan dinosaurs. (1st September 2020) - Wang, Xuri; Huang, Jiandong; Kundrát, Martin; Cau, Andrea; Liu, Xiaoyu; Wang, Yang; Ju, Shubin
Graphical abstract: Highlights: A new genus of Jeholornithiformes from the Jehol Biota in China. The earliest occurrence of fused pelvis during the evolution from non-avian dinosaurs to birds. The skeletal reinforcement occurred during the juvenile ontogeny in some Jeholornithiformes. Abstract: A new jeholornithiform – Kompsornis longicaudus gen. et sp. nov. – is reported based on a nearly complete specimen from the Jehol Biota in western Liaoning, China. Comprehensive comparisons and phylogenetic analysis, including all published species of Jeholornithiformes, are provided and indicate that Shenzhouraptor sinensis, Jeholornis prima, Jixiangornis orientalis, Jeholornis palmapenis and Jeholornis curvipes are all valid species of this clade, but that Dalianraptor cuhe is regarded as a nomen dubium . In particular, K. longicaudus possesses completely fused sternum and pelvis, a combination of advanced features that is for the first time recognized among jeholornithiforms and non-pygostylian avialans. The osteohistological investigation suggests that the skeletal reinforcement occurred during the juvenile ontogeny in some Jeholornithiformes. Therefore, the new discovery further enriches the diversity of Jeholornithiformes and suggests an unexpected developmental disparity in ossification patterns along the lineage from non-avian dinosaurs to birds.